Sistem Pendukung Keputusan Pemilihan Kamar Hotel Terbaik Di Kota Medan Dengan Menggunakan Metode Vikor - Bako, Sridewi; Lubis, Nurhamidah (JURIKOM (Jurnal Riset Komputer), 2018)
Hotel is one of the places needed as lodging facilities. Hotels in the city of Medan has also grown very rapidly. Information about the hotels - hotels in the city of Medan can be found in various websites. Decision support system is also a computer-based information system for decision-making management that handles semi-structured problems. To obtain the right hotel data and meet the expected criteria of visitors made a system that can input and update the completeness of their hotel data to in a form that has been provided. Thus, prospective visitors can obtain complete information about the data - hotel data in the city medan.Salah one method in the choice of hotel rooms in the city of this field is using the method VIKOR (Vlse Kriterijumska Optimizacija Kompromisno Resenje in Serbia). VIKOR method is a method of decision analysis with multi attribute decision making.